2018
DOI: 10.1104/pp.18.00577
|View full text |Cite
|
Sign up to set email alerts
|

A GPI Signal Peptide-Anchored Split-Ubiquitin (GPS) System for Detecting Soluble Bait Protein Interactions at the Membrane

Abstract: Article free via Creative Commons CC-BY 4.0 license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The Qa-SNARE HabcΔ or the so-called Sp3 fragments retain the interactive surfaces associated with cognate partner binding; however, they lose interactions with high-M r regulatory proteins and ion transporters (Kargul et al, 2001). We used the yeast GPI signal peptide-anchored split-ubiquitin (GPS) system, which allows detection of soluble bait protein binding (Zhang et al, 2018), to test interactions of SYP132 HabcΔ . We observed that SYP132 HabcΔ retains one-to-one binding with the cognate SNAREs SNAP33 or VAMP721 and with the full-length SYP132 (Supplemental Fig.…”
Section: Syp132 Affects Aha1 Internalization From the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The Qa-SNARE HabcΔ or the so-called Sp3 fragments retain the interactive surfaces associated with cognate partner binding; however, they lose interactions with high-M r regulatory proteins and ion transporters (Kargul et al, 2001). We used the yeast GPI signal peptide-anchored split-ubiquitin (GPS) system, which allows detection of soluble bait protein binding (Zhang et al, 2018), to test interactions of SYP132 HabcΔ . We observed that SYP132 HabcΔ retains one-to-one binding with the cognate SNAREs SNAP33 or VAMP721 and with the full-length SYP132 (Supplemental Fig.…”
Section: Syp132 Affects Aha1 Internalization From the Plasma Membranementioning
confidence: 99%
“…Protein-protein interactions were done for SYP132 ΔC and SYP132 HabcΔ as baits in vector pEXG2Met-Dest and for SYP132, VAMP721, and SNAP33 as prey in vector pNX35-Dest (Grefen et al, 2009). The yeast GPS assay was performed as described (Zhang et al, 2018). The bait constructs were transferred in yeast strain THY.AP4, and prey constructs were transferred in THY.AP5.…”
Section: Yeast Gps Systemmentioning
confidence: 99%
“…Therefore, we examined channel binding with these proteins. For mbSUS assays with the otherwise soluble baits SNAP33 and SEC11, we incorporated a glycosylphosphatidylinositol (GPI) anchor (Zhang et al, 2018) to express the corresponding protein fusions with NubG-X fusions of the full-length and truncated channel preys. Again, we recovered growth of the diploid yeast with the KC1 truncations, provided that residues 65 to 89 were present in each of the Nub-K 1 channel fusions (Fig.…”
Section: Vamp721 Snap33 and Sec11 Bind The K 1 Channel Vsdmentioning
confidence: 99%
“…A to C, Yeast mating-based split-ubiquitin assay for interaction of the VAMP721, SNAP33, and SEC11 fusions with KC1 and with Ala substitutions of key residues at the cytosolic face of the VSD as bait with Y-Cub fusions. VAMP721, SNAP33, and SEC11 as NubG-X prey fusions and with SNAP33 and SEC11 anchored via the GPI signal peptide (Zhang et al, 2018). Positive and negative controls are included in Supplemental Figure S1.…”
Section: Vamp721 Snap33 and Sec11 Bind The K 1 Channel Vsdmentioning
confidence: 99%
See 1 more Smart Citation